Efficacy of Pre-mixed Fungicides Against Rhizoctonia solani and Macrophomina phaseolina Isolated from Soybean - Karoda, Chetan; Amrate, Pawan K.; Lovewanshi, Laxman Singh; Patidar, Shubham; Kharte, Sanjay (International Journal of Economic Plants, 2025)
The experiment was conducted in 2022 (July to December) at J.N.K.V.V., Jabalpur, Madhya Pradesh, India to explore the efficacy of new combo agrochemicals against soil borne phytopathogenic fungi,i.e. Rhizoctonia solani and Macrophomina phaseolina. The pathogens were isolated from infected soybean plants and identified based on cultural and morphological characteristics. Five combo fungicides/ agrochemicals were tested based on their active ingredients at 50 and 100 ppm in four replications. The mycelial development of R. solani was significantly inhibited by penflufen 13.28%+trifloxystrobin 13.28% FS (100%) and thiophanate methyl 45%+pyraclostrobin 5% FS (100%), carboxin 37.5%+thiram 37.5% DS (88.33%) and carbendazim 12%+mancozeb 63% WP (80.55%) at 100 ppm. Whereas mycelial development of M. phaseolina was entirely inhibited by penflufen13.28%+trifloxystrobin 13.28% FS, thiophanate methyl 45%+pyraclostrobin 5% FS and carboxin 37.5%+thiram 37.5% DS at 100 ppm. Penflufen 13.28%+trifloxystrobin 13.28% FS completely checked both pathogen’s mycelial development even at 50 ppm. The significant lowest growth inhibition of R. solani (45.83%) and M. phaseolina (50.27%) was recorded by azoxystrobin 2.5%+thiophanate methyl 11.25%+thiamethoxam 25% FS at 50 ppm. Efficient combo fungicides in the present investigation could be tested against other fungal pathogens and applied as a seed treatment to reduce the fungal infection in the early stages of crops.